Greenland precipitation trends in a long‐term instrumental climate context (1890–2012): evaluation of coastal and ice core records. (29th March 2014) - Mernild, Sebastian H.; Hanna, Edward; McConnell, Joseph R.; Sigl, Michael; Beckerman, Andrew P.; Yde, Jacob C.; Cappelen, John; Malmros, Jeppe K.; Steffen, Konrad
ABSTRACT Here, we present an analysis of monthly, seasonal, and annual long‐term precipitation time‐series compiled from coastal meteorological stations in Greenland and Greenland Ice Sheet (GrIS) ice cores (including three new ice core records from ACT11D, Tunu2013, and Summit2010). The dataset covers the period from 1890 to 2012, a period of climate warming. For approximately the first decade of the new millennium (2001–2012) minimum and maximum mean annual precipitation conditions are found in Northeast Greenland (Tunu2013 c. 120 mm water equivalent (w.e.) year−1) and South Greenland (Ikerasassuaq: c. 2300 mm w.e. year−1), respectively. The coastal meteorological stations showed on average increasing trends for 1890–2012 (3.5 mm w.e. year−2) and 1961–2012 (1.3 mm w.e. year−2). Years with high coastal annual precipitation also had a: (1) significant high number of precipitation days (r2 = 0.59); and (2) high precipitation intensity measured as 24‐h precipitation (r2 = 0.54). For the GrIS the precipitation estimated from ice cores increased on average by 0.1 mm w.e. year−2 (1890–2000), showing an antiphase variability in precipitation trends between the GrIS and the coastal regions. Around 1960 a major shift occurred in the precipitation pattern towards wetter precipitation conditions for coastal Greenland, while drier conditions became more prevalent on the GrIS. Differences in precipitation trends indicate a heterogeneous spatial distribution of precipitation in Greenland. An Empirical Orthogonal Function analysis reveals a spatiotemporal cycle of precipitation that is linked instantaneously to the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation and with an ∼6 years lag time response to the Greenland Blocking Index.